Effector profiles distinguish formae speciales of Fusarium oxysporum. (29th July 2016) - van Dam, Peter; Fokkens, Like; Schmidt, Sarah M.; Linmans, Jasper H.J.; Kistler, H. Corby; Ma, Li‐Jun; Rep, Martijn
Summary: Formae speciales (ff.spp.) of the fungus Fusarium oxysporum are often polyphyletic within the species complex, making it impossible to identify them on the basis of conserved genes. However, sequences that determine host‐specific pathogenicity may be expected to be similar between strains within the same forma specialis . Whole genome sequencing was performed on strains from five different ff.spp. ( cucumerinum, niveum, melonis, radicis‐cucumerinum and lycopersici ). In each genome, genes for putative effectors were identified based on small size, secretion signal, and vicinity to a "miniature impala" transposable element. The candidate effector genes of all genomes were collected and the presence/absence patterns in each individual genome were clustered. Members of the same forma specialis turned out to group together, with cucurbit‐infecting strains forming a supercluster separate from other ff.spp. Moreover, strains from different clonal lineages within the same forma specialis harbour identical effector gene sequences, supporting horizontal transfer of genetic material. These data offer new insight into the genetic basis of host specificity in the F. oxysporum species complex and show that (putative) effectors can be used to predict host specificity in F. oxysporum .